Ecological Studies on Village Grazinglands Around Bellary - Prajapati, M C; Nambiar, K T N; Rao, P Bhaskara; Thippannavar, B S (Annals of Arid Zone, 2016)
Ecological studies on eight village grazinglands around Bellary representing two soil types viz. heavy and medium and four magnitudes of grazing-stress viz. protected, moderate, heavy and very heavy have brought out very clear relationships existing between the soil, the plant and the grazing-stress. Heavy soils sustain luxuriant growth of greater number of perennial grasses and other edible forage species and ultimately receive higher vegetative cover and yield more airdry pasturage as compared to the same by medium soils. Fifteen years closure on heavy soils resulted into climax type Dichanthium- Ersmopogon community forming an "Excellent" condition class grassland while four years closure on medium soils brought up sub-climax type Chrysopogon-Heteropogon community forming a "’Fair" condition class of grassland. The unsystematic and continuous grazing resulted into retrogression of pasturages under all the magnitudes of grazing-stress on both soil types. The extent of deterioration in grassland condition increased with the increase in magnitude of grazing-stress.